Law Enforcement in the Case of Racist Hate Speech by a Police Officer's Child: An Analysis of Multiple Articles in the ITE Law, the Criminal Code, the Criminal Procedure Code, and Human Rights Protection - Afdhal Mahatta; Tazkiyah; Corny Rachmawati; Khaerul Anwar; Alexander Joshua Pratama (Jurnal Smart Hukum (JSH), 2027)
This research analyzes the legal case of a racist contest content created by a female student with initials L, the child of a Police officer, which went viral in May–June 2026. Using normative-juridical research method with statutory, case, and conceptual approaches, this study examines the application of Article 28 paragraph (2) of the ITE Law from a criminal law perspective and analyzes the potential for tort claims (Article 1365 of the Indonesian Civil Code) and defamation claims (Article 1372 of the Indonesian Civil Code) that can be filed by victims. This research also analyzes the impact of Constitutional Court Decision Number 105/PUU-XXII/2024, international legal frameworks (Rabat Plan of Action, ICCPR, ICERD, Siracusa Principles), and various moral, ethical, and legal impacts of this case. The results show that: (1) L's content fulfills both criminal elements and tort elements; (2) the non-detention decision is formally in accordance with the Criminal Procedure Code but raises controversy; (3) Constitutional Court Decision 105/2024 narrows the interpretation of hate speech articles; (4) the L case has broad impacts on national unity, serves as a test for police reform, and raises serious moral and ethical concerns; (5) victims have a strong potential for tort claims to obtain material and immaterial damages. This research recommends: (1) regulatory harmonization; (2) strengthening legal process transparency; (3) strict law enforcement; and (4) improving public digital literacy